Tindak Tutur Direktif pada Lagu Daerah Bolaang Mongondow Bertema ‘Nasihat Orang Tua’ - Andiani Rezkita Nabu (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2020)
As one of the cultural products, the Bolaang Mongondow regional song was created based on social interaction between the Bolaang Mongondow tribal community and its cultural environment. So it is not surprised that regional song lyrics has its own uniqueness compared to other types of discourse. The purpose of this study is to investigate the types and meanings of directive utterances that exist in the discourse of the regional song lyrics of Bolaang Mongondow with the theme "parents’ advices". As a qualitative descriptive study, this research uses the simak method and simak bebas libat cakap technique to collect the data. The source of data of this study is Bolaang Mongondow’s regional songs which means ‘parents’ advices’ such as Tano-tanobon (Remember in your heart), Moraoi (So far away), Batondon (Rise Up), and Umolot (My country). Finally, this study found that the directive utterances in the songs are imperative and declarative sentences which mean for inviting, advising, forbiding, and ruling.